The Influence of Village Apparatus Competence on Quality of Village Financial Reports In Tanjungmedar District, Sumedang Regency - Suci Fitriani Hidayat; Ayi Srie Yuniawai; Apiatno (LPPM Universitas Sebelas April, 2020)
This study aims to determine the influence of village apparatus competence on the quality of village financial reports in Tanjungmedar District, Sumedang Regency. This study includes a quantitative survey method using a questionnaire with a sample of 27 village officials. The questionnaire was tested for validity and reliability. The test equipment used in this study is to use the classical assumption test, namely the normality of the data. The data analysis method used was simple linear regression analysis and correlation analysis. The results obtained from this study indicate that the village apparatus in Tanjungmedar District, Sumedang Regency can be said to be competent. With a total score for the variable (X) of 1,847 which is included in the very high category. Village financial reports in Tanjungmedar District, Sumedang Regency can be said to be of high quality. With a total variable score (Y) of 948 which is included in the high category. The Competence of Village Apparatus (X) has a positive and significant influence on the Quality of Village Financial Reports (Y) in Tanjungmedar District, Sumedang Regency. The results of hypothesis testing with t-test showed tcount > ttable (2,399>1,708) and had a coefficient of determination of 18.7% with a significance of 0.024 <0.05.